2020
DOI: 10.1177/1687814020946131
|View full text |Cite
|
Sign up to set email alerts
|

Noise reduction in high-speed train gangways using fairings and side barriers

Abstract: Interior noise in high-speed trains creates passenger discomfort and fatigue. In particular, the noise generated around the gangway between carriages tends to be easily transmitted to the passenger spaces due to the large noise component in the low-frequency region. In addition, the noise from the between-cars space around the gangway exterior tends to increase significantly when the high-speed train is travelling inside a tunnel. Therefore, this study analyses the cause of the noise generated in the gangways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The length of China’s high-speed railway and the speed of railway vehicles continue to grow, and some aerodynamics and wheel/rail wear are key scientific and technical problems (Jin, 2018; Wang et al, 2022). The internal noise of flow-induced vibration (Kim et al, 2020; Noh, 2020) and wheel–rail wear in high-speed operation (Chiello et al, 2022; Thompson and Jones, 2000) directly affect the riding quality of the train, which is an urgent problem to be solved in the development of high-speed trains.…”
Section: Introductionmentioning
confidence: 99%
“…The length of China’s high-speed railway and the speed of railway vehicles continue to grow, and some aerodynamics and wheel/rail wear are key scientific and technical problems (Jin, 2018; Wang et al, 2022). The internal noise of flow-induced vibration (Kim et al, 2020; Noh, 2020) and wheel–rail wear in high-speed operation (Chiello et al, 2022; Thompson and Jones, 2000) directly affect the riding quality of the train, which is an urgent problem to be solved in the development of high-speed trains.…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, it was confirmed that indoor noise can be significantly reduced when side barriers are installed at the bellows to minimize the inflow of vehicles. 13 However, research on improving noise performance by changing the structural body of the bellows of railway vehicles is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was confirmed that the noise in the low-frequency region, which rapidly increases while passing through a tunnel, can be blocked by blocking the inflow of noise through the side barrier and pairing. 21…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was confirmed that the noise in the low-frequency region, which rapidly increases while passing through a tunnel, can be blocked by blocking the inflow of noise through the side barrier and pairing. 21 This study aims to reduce the low-frequency noise of a railway vehicle gangway. In particular, in this study, a new approach was adopted to improve the transmission loss in a specific frequency domain by using a multilayer resonance panel, which has not been previously applied to the bellows of railway vehicles.…”
Section: Introductionmentioning
confidence: 99%